2018
DOI: 10.3892/ijmm.2018.3643
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of microsatellite instability‑associated pathways and genes in gastric cancer

Abstract: The aim of the present study was to reveal the potential molecular mechanisms of microsatellite instability (MSI) on the prognosis of gastric cancer (GC). The investigation was performed based on an RNAseq expression profiling dataset downloaded from The Cancer Genome Atlas, including 64 high-level MSI (MSI-H) GC samples, 44 low-level MSI (MSI-L) GC samples and 187 stable microsatellite (MSI-S) GC samples. Differentially expressed genes (DEGs) were identified between the MSI-H, MSI-L and MSI-S samples. Pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…In addition, the detailed molecular mechanism that MSI patterns affect the prognosis of GC patients was systematically researched among 295 patients by Hang et al (2018). The results indicated that the effect of MSI on the prognosis of GC patients may be mediated by ten important pathways, including measles, antigen processing and presentation, rheumatoid arthritis, phagosome, systemic lupus erythaematosus, herpes simplex infection, inflammatory bowel disease, tuberculosis, type I diabetes mellitus, and toxoplasmosis pathways.…”
Section: The Correlation Between Msi and The Biological Behaviour Of mentioning
confidence: 99%
“…In addition, the detailed molecular mechanism that MSI patterns affect the prognosis of GC patients was systematically researched among 295 patients by Hang et al (2018). The results indicated that the effect of MSI on the prognosis of GC patients may be mediated by ten important pathways, including measles, antigen processing and presentation, rheumatoid arthritis, phagosome, systemic lupus erythaematosus, herpes simplex infection, inflammatory bowel disease, tuberculosis, type I diabetes mellitus, and toxoplasmosis pathways.…”
Section: The Correlation Between Msi and The Biological Behaviour Of mentioning
confidence: 99%
“…Microsatellite instability (MSI) is an important indication of the DNA mismatch repair deficiency, and therefore it is perceived as a factor in the expeditive collection of genetic changes in the gastric carcinogenesis process [ 32 ]. Hang et al, 2018 [ 33 ] presented the molecular mechanisms of of microsatellite instability (MSI) and its importance in GC prognosis. Next generation sequencing data of the whole transcriptome were investigated from The Cancer Genome Atlas (TCGA), covering 64 high-level MSI (MSI-H) gastric cancer samples, 44 low-level MSI (MSI-L) and 187 stable microsatellite (MSI-S) gastric cancer samples [ 33 ].…”
Section: Gastric Cancers With Microsatellite Instabilitymentioning
confidence: 99%
“…Hang et al, 2018 [ 33 ] presented the molecular mechanisms of of microsatellite instability (MSI) and its importance in GC prognosis. Next generation sequencing data of the whole transcriptome were investigated from The Cancer Genome Atlas (TCGA), covering 64 high-level MSI (MSI-H) gastric cancer samples, 44 low-level MSI (MSI-L) and 187 stable microsatellite (MSI-S) gastric cancer samples [ 33 ]. The results showed that MSI status might have impact on the prognosis of GC patients, partially through the inflammatory bowel disease, antigen processing and presentation, measles, toxoplasmosis, and herpes simplex infection pathways.…”
Section: Gastric Cancers With Microsatellite Instabilitymentioning
confidence: 99%
“…It is a potential biomarker which can be reflected in gastric cancer (GC) patients with microsatellite instability-high (MSI-H) achieve superior responses to PD-1 antibody [4]. Significant difference in prognosis can be seen with different MSI state [5]. LncRNAs data analysis done by TANRIC showed there might be a correlation existed in lncRNAs and MSI [6].…”
Section: Introductionmentioning
confidence: 99%